Deep Mapping and Screen Tourism: The Oxford of Harry Potter and Inspector Morse - James Cateridge (Humanities, 2015)
This article proposes that the experiences of screen tourists in Oxford help to create a theoretical “deep map” of the city which explores place through narrative. Building on the travel writing of William Least Heat-Moon and other recent work in the spatial humanities, two case studies of major screen tourism drivers are considered and analyzed. The British television drama Inspector Morse (1987–2000) explores the ambiguity of Oxford intellectualism through its central character. Morse’s love of high culture, especially music, provides suggestive additional layers for multimedia mapping, which are realized online through user-adapted Google Maps and geolocated images posted on the Flickr service. Harry Potter fans may not be “pure” or independent screen tourists, but they provide a wealth of data on their interactions with filming locations via social media such as Instagram. This data provides emotional as well as factual evidence, and is accumulating into an ever richer and deeper digital map of human experience.